Sociological Analysis of Divorce: A Case Study from Pokhara, Nepal - Bala, Acharya Ram (Dhaulagiri Journal of Sociology and Anthropology, 2006)
This article is based on field study among different caste and ethnic groups residing in Pokhara sub-metropolitan city of Nepal. It tries to identify the causes of divorce in those groups. Probably, it is the first sociological study on divorce based on empirical fact in Nepal, so it may contribute a little bit to the direction of the sociological study. The tradition of sociological and anthropological research on social institutions and processes is not dominant in Nepal. Sociologists have found that there are different natures of changes on social institutions, economy, culture and political structure. This is a universal phenomenon around the world. However it could be fruitful to analyze causes and consequences of the social events or changes from the sociological perspective in the different social and cultural context. This study focuses on divorce basically the legal separation of the husband and wife. However customary divorce practices are in different communities of the Nepalese society. DOI: 10.3126/dsaj.v1i0.284 Dhaulagiri Vol.1 (2005) pp.129-145